What Factors Influence Software Professionals Performance and Do Need for Achievement and Need for Social Power Moderate Performance? - Prasad H C Shiva; Suar Damdar (Emotional intelligence (Optimizing Human Performance at Work), 2012)
Purpose - This study examines the factors that influence the performance of Indian software professionals and the moderators of performance. Emotional intelligence competencies at the individual level, transformational leadership style of the team leaders and social capital among team members at the group level, and human resources management practices of software firms at the enterprise level are postulated to influence performance. Need for achievement and need for social power of software professionals are proposed to moderate such relationships. Design/methodology/approach - Data were collected from 441 software and senior software engineers from eight Indian software firms on above constructs except performance. Fifty-five team leaders assessed the performance of software and senior software engineers on 16 items. Findings - Results reveal that emotional intelligence competencies, transformational leadership, social capital, and human resource management practices directly influence performance. Emotional intelligence competencies are found to be the most important antecedent of performance. Even under low need for achievement and low need for social power, software professionals' emotional intelligence competencies and team leaders' transformational style have improved performance. Conversely, under high (low) need for achievement and high (low) need for social power, the social capital among team members and the human resources management practices of software firms have increased (attenuated/nullified) performance. Implications - Software firms can hire software professionals with high emotional intelligence competencies and mould the way of functioning of team leaders so that even under low need for achievement and low need for social power, the former can boost the performance. The firms can facilitate to build social capital among team members, and augment human resources management practices for improving performance. Originality/value - Though emotional intelligence competencies are most important predictor of performance, other factors in accordance with organizational behavior model also contribute to performance of Indian software professionals and call for attention to improve productivity.
Keywords: M15; D23; 330; Emotional intelligence competencies; Human Resource Management practices; Moderator; Performance; Social capital; Transformational leadership